Pengaruh Manajemen Waktu Terhadap Self-Efficacy Dan Motivasi Belajar Peserta Didik SMP Negeri Se-Kecamatan Ungaran Barat - Laras Anggriyani; Awalya (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine the influence of self-efficacy and learning motivation on time management among junior high school students in West Ungaran District. The background of the research stems from observations that students often struggle with managing their study time effectively, which can negatively impact academic performance. A quantitative approach with a correlational research design was employed. The sample consisted of 261 eighth-grade students, selected using probability sampling techniques. Data were collected through a closed-ended questionnaire that had been tested for validity and reliability. The data analysis technique used was multiple linear regression. The results revealed that both self-efficacy and learning motivation significantly influenced students’ time management skills, both partially and simultaneously. Among the two variables, self-efficacy showed the most dominant effect in helping students organize their study schedules, set learning priorities, and complete academic tasks on time. Meanwhile, learning motivation also contributed positively by encouraging students to use their time more effectively and stay focused on academic goals. These findings indicate that effective time management is not solely determined by technical skills such as planning or scheduling but is also influenced by internal psychological factors such as students' belief in their abilities and the drive to learn. Based on the results, it is recommended that educators and school counselors implement programs that strengthen students’ self-efficacy and foster intrinsic motivation to improve academic time management. This can ultimately support better learning outcomes and personal development among junior high school students.